PAD-4 Elevation Distinguishes Acute from Past CMV Infection in Medical Students - Murtada Wafi Beden (Indonesian Journal on Health Science and Medicine, 2026)
General Background: Cytomegalovirus (CMV) is a persistent herpesvirus with complex interactions between humoral and innate immunity. Specific Background: Neutrophil extracellular trap formation (NETosis), mediated by peptidylarginine deiminase-4 (PAD-4), is increasingly recognized in antiviral defense, yet its relation to CMV serological phases remains unclear. Knowledge Gap: The association between CMV IgM/IgG serostatus and PAD-4 activity as a surrogate marker of innate immune activation has not been well characterized in healthcare-exposed student populations. Aims: This cross-sectional study assessed CMV seroprevalence across three medical departments and examined PAD-4 levels according to CMV serology. Results: Among 300 students, overall CMV seroprevalence was 16.33%, highest in nursing (21%) and lowest in medical laboratory students (11%). PAD-4 levels were significantly higher in IgM-positive individuals than IgG-positive and seronegative peers (p=0.003), while no sex-based difference was observed. Novelty: The study links CMV serological phase to differential PAD-4 activity, indicating heightened innate activation during recent infection and relative immune quiescence in past exposure. Implications: PAD-4 may serve as a biomarker of acute CMV-related innate responses and supports targeted infection-control awareness in healthcare training environments. Highlights: CMV seroprevalence differed across healthcare training departments. PAD-4 levels peaked in IgM-positive (recent infection) students. PAD-4 showed no significant variation by sex. Keywords: Cytomegalovirus, PAD-4, NETosis, IgM/IgG Serostatus, Medical Students